The changing existence of the image of women in Motinggo Busye's novels - Pramono, Dedi; Islahuddin, Islahuddin; Lixian , Xiao (BAHASTRA, 2023)
This research aims to reveal changes in the image of women in the novel by Motinggo Busye, which was published 30 years (1960 – 1990). The theory used in this research is feminist theory. The research method uses qualitative content description. The subject of this research was carried out using a purposive sampling technique, namely the novel by Motinggo Busye which was published 30 years (1960 - 1990). The results of this research indicate a change in the image of women in providing biological material needs from aggressive, immoral and hedonistic to polite, civilized and religious.